Transient pacing pulse on the T-wave: What is the mechanism? - Yuta Sudo (Indian Pacing and Electrophysiology Journal)
A patient with a dual-chamber pacemaker for sick sinus syndrome was hospitalized for heart failure. The electrocardiography (ECG) during hospitalization displayed seemingly abnormal pacing artifacts. This report focuses on the problem-solving of an abnormal-looking paced ECG and identifies the pacemaker's operational behavior as the underlying reason.